Management of Epidermolysis Bullosa through Ayurveda- a case report of two siblings - Kuldeep Kavathiya; Jitesh Verma; Umakant Tiwari; Bharat Bhoyar; Anamika (Journal of Ayurveda and Integrative Medicine, 2025)
Epidermolysis bullosa (EB) is a group of inherited rare skin disorders that causes the skin to become fragile and blister easily due to minor trauma or friction. Blisters can appear anywhere on the body. There are limitations in treating this disease in the conventional system of medicine. This paper elaborates on the case of two siblings who presented with blisters all over the body with itching, discharge, difficulty in walking, and disfigurement of fingers, toes, and feet. Based on Ayurvedic clinical assessment, the condition was diagnosed as Kapha-pitta dominant Tridoshaja Visphota. They were treated through Ayurveda on the line of Visphota (a type of Kushtha/skin disorder) with the use of Dipana (digestion and metabolism-enhancing), Pachana (enhancing digestion), and Mridu Shodhana (mild bio-cleansing) medicines. Both patients have shown improvement with a reduction in EBDASI (Epidermolysis bullosa disease activity and scaring index) from 174 to 45 and 176 to 39, respectively, in the first and second sibling with 4 months of ayurvedic medication. No relapse was seen in both patients during the next one year. The case study is unique as EB is a genetic disorder with limitations in its management in the conventional system of medicine. Moreover, the authors could not find any published case of EB managed through Ayurveda treatment. Thus, it opens new areas of research in the management of EB through traditional systems of medicine like Ayurveda.